PERAN BRAND IMAGE, KUALITAS PRODUK, HARGA DAN GAYA HIDUP GENERASI Z TERHADAP KEPUTUSAN PEMBELIAN IPHONE: (Studi Pada Mahasiswa Universitas Dian Nuswantoro Pengguna Iphone) - Wijanarko, Danang; Mahmud, Mahmud; Haziroh, Awanis Linati; Fatmawati, Elia Resha (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study examines the impact of brand image, product quality, price, and lifestyle on iPhone purchasing decisions among Generation Z, specifically Dian Nuswantoro University students. Using a quantitative approach with an questionnaire survey distributed to 133 students, the data were analyzed through Partial Least Square (PLS). The results revealed that brand image, product quality, price, and lifestyle positive and significantly influence iPhone purchasing decisions. A strong brand image boosts buying interest, product quality builds confidence, price aligns with perceived benefits, and lifestyle affects preferences based on social status. The findings suggest that Apple should focus on brand image, product quality, and pricing strategies tailored to young consumers.